1993
DOI: 10.1002/nt.2620010506
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the major component in white snakeroot that is toxic after microsomal activation: Possible explanation of sporadic toxicity of white snakeroot plants and extracts

Abstract: Tremetone, the major toxic component in white snakeroot (Eupatorium rugosum Houtt) extracts, was isolated following an in vitro bioactivity assay. Microsomal activation was required to produce a product toxic to murine melanoma (B16F1) cells as well as five other mammalian cell cultures. The metabolic activation product(s) of tremetone is suspected to be responsible for the toxic activity of the plant. Tremetone is also smoothly converted to dehydrotremetone in the plant and cell free homogenates, and readily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 20 publications
0
27
1
Order By: Relevance
“…A previous study demonstrated that in vitro microsome-activated tremetone is cytotoxic, but dehydrotremetone was not. 2,3 This suggests that an ''activated'' tremetone metabolite is responsible for white snakeroot toxicity. However, this has not been confirmed experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that in vitro microsome-activated tremetone is cytotoxic, but dehydrotremetone was not. 2,3 This suggests that an ''activated'' tremetone metabolite is responsible for white snakeroot toxicity. However, this has not been confirmed experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 Various toxins have been described in rayless goldenrod. 3,5,6,9,16 In addition to the previously mentioned tremetol, 5,6 several monoterpenes, sesquiterpenes, 16 and essential oils 3 have also been described. In vitro studies using a tremetol mixture suggests that at least 1 component of this mixture or of its metabolites inhibits oxidative phosphorylation, most likely by inhibiting the tricarboxylic acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of toxic tremetone (1) to nontoxic dehydrotremetone (2) was offered as an explanation for the sporadic toxicity of white snakeroot and rayless goldenrod. 10,11 In general, subsequent review literature on white snakeroot toxicity has perpetuated these reports and their suppositions: tremetol or tremetone (1) are the toxic principles; white snakeroot plants lose toxicity when dried; 12−15 and tremetone (1) is converted to dehydrotremetone (2) during isolation. 13 Additionally, it is reported that rayless goldenrod contains the same or similar toxic principle as white snakeroot.…”
Section: ■ Introductionmentioning
confidence: 98%
“…11 In plants, tremetone is converted to dehydrotremetone, but these microsomal activation studies suggest that dehydrotremetone is not physiologically active. 11 In plants, tremetone is converted to dehydrotremetone, but these microsomal activation studies suggest that dehydrotremetone is not physiologically active.…”
Section: Toxicokineticsmentioning
confidence: 99%